Rethinking Point Cloud Filtering: A Non-Local Position Based Approach. (March 2022) - Wang, Jinxi; Jiang, Jincen; Lu, Xuequan; Wang, Meili
Abstract: Existing position based point cloud filtering methods can hardly preserve sharp geometric features. In this paper, we rethink point cloud filtering from a non-learning non-local non-normal perspective, and propose a novel position based approach for feature-preserving point cloud filtering. Unlike normal based techniques, our method does not require the normal information. The core idea is to first design a similarity metric to search the non-local similar patches of a queried local patch. We then map the non-local similar patches into a canonical space and aggregate the non-local information. The aggregated outcome (i.e. coordinate) will be inversely mapped into the original space. Our method is simple yet effective. Extensive experiments validate our method, and show that it generally outperforms position based methods (deep learning and non-learning), and generates better or comparable outcomes to normal based techniques (deep learning and non-learning). Highlights: A non-learning non-local non-normal approach for feature-preserving point cloud filtering. A robust search algorithm for finding non-local similar patches. An effective position update algorithm for fusing non-local similar information. Two iteration schemes for flexible use.